Geographic Information Systems and Remote Sensing Techniques in Environmental Assessment - Kenny, Frank (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1996)
Summary Digital map products and spatial inventories are becoming increasingly available from geological surveys, agricultural, natural resource, environmental, energy, transportation and forestry departments. As well there are now multitudes of specialized digital air borne and satellite image products available. This wide availability of geographically referenced data and the advances inspatial data analysis software are providing geoscientists with new tools andnew ways of viewing traditionally use ddata. Through several examples, this paper will demonstrate how remote sensing and GIS technologies can contribute to environmental assessment of an urban fringe area. Now here is the need for spatial inventories and mapping greater than in such areas, where pre-existing information becomes rapidly outdated. A 260-km2 site, north of Metropolitan Toronto was chosen as a study area. A spatial data base was constructed which included imagery from three different satellite sensors, a Digital Terrain Model (DTM), a digital drainage net work, and a digital copy of the Ontario Geological Survey's Quaternary geological map.